The Discourse of Fear in American TV Fiction: A Furedian Reading of Person of Interest - Fernández Morales, Marta; Menéndez Menéndez, María Isabel (Complutense Journal of English Studies, 2017)
Inserted in the ongoing discussion about the post-9/11 cultural archive, this paper analyzes the TV series Person of Interest (CBS, 2011–2016), created by Jonathan Nolan, through Frank Furedi’s theories about the discursive formation of fear as presented in his texts Politics of Fear. Beyond Left and Right (2005), Invitation to Terror. The Expanding Empire of the Unknown (2007), The Only Thing We Have to Fear Is the ‘Culture of Fear’ Itself (2007), and Precautionary Culture and the Rise of Possibilistic Risk Assessment (2009). We make these works converse with several American and European sociological views, offering a transnational perspective over the issues at hand. With an interdisciplinary approach and with a critical-cultural methodology supported by selected instances from the first four seasons of the show, we argue that, despite timid hints at a critique of the flawed American democracy, the show feeds into an ever-growing array of media proposals of a citizenship based on precaution, contributing to the reinforcement of the post-9/11 atmosphere of fear through a logic predicated on inevitability and a deflated sense of agency on the part of common people that discourages practices of resistance.